High‐Performance Ultraviolet Photodetector Based on a Few‐Layered 2D NiPS3 Nanosheet. (4th July 2017) - Chu, Junwei; Wang, Fengmei; Yin, Lei; Lei, Le; Yan, Chaoyi; Wang, Feng; Wen, Yao; Wang, Zhenxing; Jiang, Chao; Feng, Liping; Xiong, Jie; Li, Yanrong; et al.
Abstract : 2D materials, represented by transition metal dichalcogenides (TMDs), have attracted tremendous research interests in photoelectronic and electronic devices. However, for their relatively small bandgap (<2 eV), the application of traditional TMDs into solar‐blind ultraviolet (UV) photodetection is restricted. Here, for the first time, NiPS3 nanosheets are grown via chemical vapor deposition method. The nanosheets thinning to 3.2 nm with the lateral size of dozens of micrometers are acquired. Based on the various nanosheets, a linearity is found between the Raman intensity of specific Ag modes and the thickness, providing a convenient method to determine their layer numbers. Furthermore, a UV photodetector is fabricated using few‐layered 2D NiPS3 nanosheets. It shows an ultrafast rise time shorter than 5 ms with an ultralow dark current less than 10 fA. Notably, this UV photodetector demonstrates a high detectivity of 1.22 × 10 12 Jones, outperforming some traditional wide‐bandgap UV detectors. The wavelength‐dependent photoresponsivity measurement allows the direct observation of an admirable cut‐off wavelength at 360 nm, which indicates a superior spectral selectivity. The promising photodetector performance, accompanied with the controllable fabrication and transfer process of nanosheet, lays the foundation of applying 2D semiconductors for ultrafast UV light detection. Abstract : Herein, a high‐performance ultraviolet photodetector based on a few‐layered 2D NiPS3 nanosheet is demonstrated. NiPS3 nanosheets are first synthesized by the chemical vapor deposition method and the thickness‐dependent Raman spectra are systematically investigated. A two‐terminal device based on NiPS3 nanosheets exhibits significant spectral selectivity. A rise time shorter than 5 ms and a detectivity of 1.22 × 10 12 Jones are realized.